Spatio-temporal variability of the earth's surface temperature and the changes in land user/land cover: implications for sustainable tourism development - Garcia, David Hidalgo; Rezapouraghdam, Hamed; Hall, Colin Michael; Karatepe, Osman M.; Koupaei, Sara Naderi (Routledge Journals, Taylor & Francis Ltd, 2025)
Tourism both contributes to environmental change and is, in turn, affected by such change. One area that is of considerable significance is tourism's contribution to land use change and its subsequent impacts. Land use change, such as tourism urbanization, together with global heating leads to an increase in surface temperature and deterioration in environmental quality and human comfort levels. Understanding the implications of tourism-related land use change is therefore of considerable importance for climate adaptation. Using Landsat satellite images, the evolution of land users/covers and the temperature of the land surface between 1985 and 2020 were studied in Cyprus. The analysis of the data confirms that tourism development activities have influenced the increase in urban hotspots. This destination has experienced a 6.2 degrees C increase in average temperature and 168.8% in the urban hotspot. Based on the findings the study highlights the implications for sustainable tourism development and potential means of mitigation.
Keywords: Climate change; land cover; land surface temperature; land use; sustainable tourism; remote sensing